THE RELATIONSHIP BETWEEN POLITICIANS AND BUREAUCRATS: WHO DOMINATES? - Dumbliauskas, Vytautas (Politologija, 2015)
This article aims to answer the question, why different modern scholars undertake different positions towards who should dominate – the politicians or the bureaucrats. It depicts the transformation of the public sector in Western democracies, when elected politicians started intervening with the activities which used to be under the monopoly of professional public servants. Politicians and bureaucrats as professional groups are highly distinct. According to M. Weber, the imperative of politicians is the struggle for power, whereas bureaucrats tend to be obedient and disciplined; politicians – act in the public domain, and bureaucrats function in institutions; the working tool of politicians is their voice, whereas public servants tend to rely on the written word; politician above all things is an actor who passionately advocates for his cause, while an administrator concentrates on solving technical problems; finally, the career of a politician is uncertain, temporary and flexible, whereas bureaucrats often enjoy stability.The above defined differences led to a belief that a division of roles between politicians and bureaucrats is possible and that it can be further defined by dichotomies of end-means and values-facts. However, the article states that these dichotomies are not suitable for the analysis of a complex relationship between politicians and public servants. The goals and values of public policy are defined by both – politicians and bureaucrats, who have their own professional understanding of policy goals. In addition, during the process of implementation public servants tend to act according to their own views and their own values.Despite professional differences politicians and bureaucrats often struggle for the control over the public policy. While the first are driven by the ambition to win the upcoming elections, the latter are interested in obtaining their working position and the stability of their career. Public servants try to engage themselves in the policy-formation process, whereas politicians aim to have politically loyal or at least neutral bureaucracy. This power struggle is dominated by one side or the other because dominance is fluid and flexible, dependant on various factors. Those scholars who view public servants as more dominant emphasize the need to strengthen the political control of bureaucracy. And those who view politicians as more powerful see bureaucrats as a tool to control politicians and prevent abuse of power.